2015
DOI: 10.1111/hae.12636
|View full text |Cite
|
Sign up to set email alerts
|

How fit are children and adolescents with haemophilia in Germany? Results of a prospective study assessing the sport‐specific motor performance by means of modern test procedures of sports science

Abstract: There are a lot of publications on the physical fitness of patients with haemophilia (PWH), however, most studies only reflect individual sport-specific motor capacities or focus on a single fitness ability. They involve small patient populations. In this respect principal objective of this study was to compare the physical fitness in all respects and the body composition of young PWH to healthy peers based on the most valid data we could get. Twenty-one German haemophilia treatment centres were visited from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Decline in joint function negatively impacts HRQoL through decreased activity and participation [45,46], and deterioration in joint scores confirm the importance of lifelong prophylactic clotting factor replacement therapy [47]. Improvements in joint strength and ROM in patients with haemophilia, such as those observed through exercise therapy [45,48], have been linked with improvements in daily functioning and HRQoL [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decline in joint function negatively impacts HRQoL through decreased activity and participation [45,46], and deterioration in joint scores confirm the importance of lifelong prophylactic clotting factor replacement therapy [47]. Improvements in joint strength and ROM in patients with haemophilia, such as those observed through exercise therapy [45,48], have been linked with improvements in daily functioning and HRQoL [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in joint strength and ROM in patients with haemophilia, such as those observed through exercise therapy [45,48], have been linked with improvements in daily functioning and HRQoL [49,50]. Both generic (SF-36) and disease-specific HRQoL tools can be used to assess patients with haemophilia, dependent on the QoL domains being evaluated [49].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies verified a deficit in the basic motor functions in people with haemophilia (PwH), this is why a multimodal training is necessary. Regarding strength performance, studies have shown reduced strength in certain muscle groups and patient groups: adults with haemophilia seem to have strength deficits in the upper and lower extremities as well as in the back muscles.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, physical functioning is mainly assessed through ClinROs such as the HJHS and/or PROs such as the PedHAL or the HEP‐Test‐Q . In research or gait and motion laboratories, physical functioning is evaluated by clinimetric measures, Performance Outcomes (PerfOs) such as 1 leg stand, 6‐minute walk test or the Functional Independence Score for Hemophilia (FISH) or apparatus testing such as pedabarography, EMG or motion analysis . The self‐reported PedHAL focuses on activities of daily living such as use of transport, self‐care and household tasks, whereas the HEP‐Test‐Q assesses aspects of physical functioning based on motor ability (mobility, strength, coordination and endurance).…”
Section: Discussionmentioning
confidence: 99%
“…12 In research or gait and motion laboratories, physical functioning is evaluated by clinimetric measures, 29 Performance Outcomes (PerfOs) such as 1 leg stand, 6-minute walk test or the Functional Independence Score for Hemophilia (FISH) 30 or apparatus testing such as pedabarography, EMG or motion analysis. 31 The self-reported PedHAL focuses on activities of daily living such as use of transport, self-care and household tasks, whereas the HEP-Test-Q assesses aspects of physical functioning based on motor ability (mobility, strength, coordination and endurance). PedHAL is an internationally recognized instrument with use in clinical trials, yet there is limited published evidence of its use.…”
Section: Moreover We Found Low Correlations Between the Hep-testmentioning
confidence: 99%